PENGARUH PERSENTASE PEREKAT POLYETHYLENE TERHADAP SIFAT FISIS DAN MEKANIS WOOD PLASTIC COMPOSITE (WPC) BERBAHAN BAKU SERBUK KAYU KERUING (Dipterocarpus Spp.) - Susilastri Susilastri; Aldri Frinaldi; Dasman Lanin; Rembrandt Rembrandt; Genius Umar; Firman Hidayat; Yefnika Fazira (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to determine the effect of polyethylene (HDPE) adhesive percentage on the physical and mechanical properties of Wood Plastic Composite (WPC) made from Dipterocarpus spp. (keruing) sawdust. The research is driven by the decreasing availability of natural wood and the increasing volume of plastic waste, highlighting the need for innovative, environmentally friendly, and sustainable material alternatives. The method used was a Completely Randomized Design (CRD) with five treatment compositions of keruing sawdust and polyethylene: A (80:20), B (75:25), C (70:30), D (65:35), and E (60:40), each with three replications. The observed parameters included physical properties (density, moisture content, water absorption, and thickness swelling) and mechanical properties (Modulus of Rupture/MOR and Modulus of Elasticity/MOE). Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level.The results showed that increasing the proportion of polyethylene significantly affected most physical and mechanical properties of WPC. The highest density (1.1 g/cm³) was observed in treatments D and E, although not significantly different statistically. Moisture content, water absorption, and thickness swelling decreased significantly with increased adhesive. The best performance was found in treatment E (60% wood, 40% polyethylene) with moisture content at 1.54%, water absorption at 197.82%, and thickness swelling at 9.19%, meeting the JIS A 5908-2003 standard. Mechanically, MOR and MOE values also increased, with the highest values recorded at 99.47 kgf/cm² and 30 kgf/cm², respectively, although still below JIS standards. In conclusion, increasing the proportion of polyethylene adhesive improves both physical and mechanical properties of keruing-based WPC. A formulation of 60% keruing sawdust and 40% polyethylene is recommended as the optimal composition for producing high-quality WPC from wood and plastic waste. Keyword: Wood Plastic Composite, polyethylene, keruing sawdust, physical properties, mechanical properties, HDPE.